Hvilket barn? Om barn, barndom og barnehage - Agnes Andenæs (Nordisk Barnehageforskning, 2012)
Title: What kind of a child? On children’s everyday life, Early Childhood Education, and psychological development Abstract: Public discussions about day care more or less explicitly refer to models about children’s development. My argument is that the field of Early Childhood Education does need understandings offered by the discipline of developmental psychology, but that the hegemonic ones strongly restrict ways of talking about what is going on at the day care institutions, and what day care means to the participants, included parents and other caretakers. A more context sensitive and meaning making oriented version of developmental psychology is presented, and empirical examples are used to demonstrate how this way of understanding children widens up ways of talking about day care: as an arena for children’s participation, as a link in parents’ chain of care for their child, and as a meeting point for diversity. Keywords: Developmental psychology; Day care; Everyday life; Parenthood; Chain of care; Social participation